PENGARUH SOLVABILITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PERATAAN LABA - Nur Fitri; Eyo Asro Sasmita; Amir Hamzah (Jurnal Riset Keuangan dan Akuntansi, 2018)
This study aimed to know the influence of slovency, probability and size company of income smoothing in the sector industrial goods comsumption listed on the indonesian stock exchange. The sample in this study is determined by Purposive Sampling method based on the criteria of the consumer goods sector companies listed on the stock exchange indonesian and never delisted during the period 2014-2017, to obtained a sample of 26 company. This research used regression model of panel data. The result of this research concludes the result of f test jointly Solvabilitas, Profitability and Size have significant influence to Profit Income. And t test result (partial) Partially variable Solvability and Size Company have positive and significant effect to income smoothing. While Profitability variable has a negative and significant effect to income smoothing. The value of determination coefficient is 91,14% and it can be concluded that Debt to Equity Ratio, Profitability, and Size able to explain variable of Benefit of Earnings.Keywords: Income Smoothing, Solvency, Profitability and Company Size